Aspek Estetis dalam Cerita Pendek â€œInu to Hito to Hanaâ€ Karya Ogawa Mimei - Priventa, Hendrike (Chi'e: Journal of Japanese Learning and Teaching, 2020)
The short story "Inu to Hito to Hana" by Ogawa Mimei is a simple story that is full of elements of ethics and aesthetics. The purpose of this study is to describe the aesthetic aspects of the short story "Inu to Hito to Hana". The method used is literature study using an aesthetic identity approach. The results of this study can be seen from aesthetic aspects, namely 1) language style, 2) symbols, 3) imagination process, and 4) philosophical values. Keywords : Aesthetic aspects, aesthetic identity, ethics, Japanese short story